Expansão urbana e seus efeitos sobre a mobiidade e acessibilidade avaliada com o auxílio dos sistemas de informação geográfica (SIG) em Teresina - PI - Nicia Bezerra Formiga Leite (2013)
A ex The expansion of urban areas, together with population growth of most Brazilian cities, has exerted strong pressure on urban basic infrastructure, marked by insufficient care and the inefficiency of public service, which has caused difficulties in urban mobility and accessibility. To evaluate spatially the territorial organization based on accessibility and mobility, has been used the Geographic Information Systems (GIS) coupled with multi-criteria analysis. Therefore, the aim of this study was to evaluate urban mobility and accessibility of the city of Teresina focusing on the production of urban space and the use of geoprocessing techniques and multicriteria analysis. For this purpose, we carried out initially, a conceptual approach to the production of urban space, directed primarily to the city of Teresina. After that, we provided the processing and analysis of the urban data compiled by the intersection of information obtained. In this way, it was combined the various dimensions of urban analysis, of the physical and anthropic natural environment, which affect mobility and accessibility, using a computer system for spatial analysis, in order to guide the planning and urban management. We considered the ray coverage of municipal utilities for evaluation of accessible areas and subsequent analysis of urban mobility in the city of Teresina. The results were presented by a collection of thematic maps highlighting the following: suitability maps related to the factors of local public services, such as the distance of the health clinics, schools, commercial and industrial areas, among others, in addition to suitability map of areas with greater access to local public services and the map of the urban accessibility index. It was observed that the suitability of the areas of accessibility to the city of Teresina is variable and depends mainly on the location of public services and not just for being inserted into peripheral areas and low purchasing power, because even in the central areas there is damage of the accessibility. It is important to mention that the study of urban mobility and accessibility and its interface with the technologies of the use of GIS systems tends to provide facilitators for the analysis and understanding of urban space. Moreover, the methods employed in this work can be used as support for other studies that plan to evaluate the urban territorial management aiming to implement public policies that help in sustainable urban development.